The prevalence and associated factors of intracranial lesions on mri and the accuracy of flair sequence in patients with headache but no neurological deficit. - Jaafar, Wan Daizyreena Wan (2007)
OBJECTIVES: The objectives of this study were to detennine prevalence and associated factors of intracranial lesions on :MRI examination and the accuracy of FLAIR in detecting intracranial lesions in patients with headache but no neurological deficit. METHOD: A retrospective and prospective cross-sectional study was perfonned over 51 months from 1 st June 2002 until 30th September 2006. One hundred and forty-three patients with headache but no neurological deficit aged 13 years old and above who had underwent routine :MRI examination of brain in Hospital University Sains Malaysia were included into this study. For each case, FLAIR sequence and complete brain series were reviewed separately at different times by two radiologists. RESULTS: Prevalence of intracranial lesions on complete MRI sequence was 18.9% (95% CI: 0.06, 0.32). The sensitivity for FLAIR was 92.6% and the specificity of 92.2%. Age more than 40 years and experiencing headache between 3 - 6 months were found to have association with abnonnalities detected with adjusted OR 0.191 (0.07, 0.51) and 4.86 (1.37, 17.26) respectively. Intracranial abnormalities detected by FLAIR sequence were white matter lesions, meningioma, teratoma, meningo-encephalitis and intracranial haemorrhages. On the other hand, FLAIR missed to detect a small sub-ependymal nodule and arachnoid cyst in CSF spaces. CONCLUSION: Since FLAIR sequence is sensitive in detecting intracranial lesions, it can be used as a screening sequence in patients with headache but no neurological deficit. The MR examination time can be shortened and the number of patients for MR examination per day can be increased.